Microbiome Applications from Lab to Field: Facing Complexity. (March 2019) - Sessitsch, Angela; Pfaffenbichler, Nikolaus; Mitter, Birgit
Abstract : Plant microbiota are the subject of new product developments, primarily aimed at improving plant health, nutrition, and stress resilience. However, current application of microbials in the field faces multiple challenges and we propose that multiple aspects need to be considered, for example, understanding the complexity and ecological behaviour of natural microbiota.